Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1063/1.1310626
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance effect and interlayer coupling of (Ga, Mn)As trilayer structures

Abstract: We have investigated the magnetic and magnetotransport properties of (Ga, Mn)As/(Al, Ga)As/(Ga, Mn)As semiconductor-based magnetic trilayer structures. We observe a weak ferromagnetic interlayer coupling between the two ferromagnetic (Ga, Mn)As layers as well as magnetoresistance effects due to spin-dependent scattering and to spin-dependent tunneling. Both the coupling strength and the magnetoresistance ratio decrease with the increase of temperature and/or the increase of Al composition of the nonmagnetic (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
81
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(85 citation statements)
references
References 16 publications
1
81
3
Order By: Relevance
“…In contrast, in the (Ga,Mn)As-based semiconductor ferromagnetic/ nonmagnetic systems interlayer coupling of opposite FM sign was observedby magnetic measurements [13][14][15], neutron diffraction [16], and polarized neutron reflectometry [17]. These structures differ from the previously considered EuS-based ferromagnetic semiconductor multilayers by many aspects, which all can affect the IEC.…”
Section: Interlayer Coupling and The Tight-binding Modelmentioning
confidence: 78%
See 1 more Smart Citation
“…In contrast, in the (Ga,Mn)As-based semiconductor ferromagnetic/ nonmagnetic systems interlayer coupling of opposite FM sign was observedby magnetic measurements [13][14][15], neutron diffraction [16], and polarized neutron reflectometry [17]. These structures differ from the previously considered EuS-based ferromagnetic semiconductor multilayers by many aspects, which all can affect the IEC.…”
Section: Interlayer Coupling and The Tight-binding Modelmentioning
confidence: 78%
“…This so-called tunnel anisotropic magnetoresistance (TAMR) effect was observed when the saturation magnetization direction was changed in-plane [9][10][11] as well as when it was turned perpendicular to the magnetic layer [11,12]. It was also shown that the magnetization vectors of consecutive (Ga,Mn)As ferromagnetic layers separated by nonmagnetic spacers in a multilayer structure are correlated by an interlayer coupling [13][14][15][16][17] and structures exhibiting giant magnetoresistance (GMR) were obtained [14].…”
Section: Introductionmentioning
confidence: 97%
“…8,9 A problem will also exist for multilayer semiconductor heterostructures, where the composition variation between nearest layers is about the same with a few percent difference in solid solution content. 10 Hence, the change in density is so small that the sensitivity of the XRR method may be insufficient for characterization of such materials. Thus, the search for a more direct and established approach to characterization of nm-thick layers in a variety of multilayered structures, which is sensitive and independent on optical properties, is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Chiba et al [21] observed a TMR ratio of 5.5% at 20 K in a GaMnAs tunnel junction. Also, Tanaka and Higo [22] reported TMR ratios more than 70% at 8 K in GaMnAs/AlAs/GaMnAs heterostructures.…”
Section: Introductionmentioning
confidence: 99%